Patterns and Determinants of Suicidal Ideation Outcomes among University Students: A Socio-demographic and Academic Contextual Analysis - Olaseni, Abayomi O.; Agesin, Bankole E.; Popoola, Abiola O.; Alliu, Sadiat I.; Fagbenro, Dare A.; Yaru, M.A. (Journal of Posthumanism, 2026)
Suicidal ideation remains a critical public health concern among university students, particularly in low- and middle-income countries where empirical evidence is still emerging. This study examined the patterns and determinants of suicidal ideation among undergraduate students, with specific emphasis on sociodemographic characteristics and academic-contextual factors. A cross-sectional survey design was adopted, and data were collected from 2,366 university students. Suicidal ideation was conceptualised into three categories: past suicidal ideation, current suicidal ideation, and no suicidal ideation. Sociodemographic variables (age grade, gender, and family structure) and academic factors (academic level, faculty affiliation, and cumulative grade point average [CGPA]) were analysed using chi-square statistics and effect size measures. The results showed that suicidal ideation varied significantly across age grades, academic levels, faculty affiliations, family structures, and CGPA classifications. Younger students and those in the early stages of university education reported higher proportions of both past and current suicidal ideation. Pronounced faculty-based differences were observed, indicating the potential role of discipline-specific academic demands and stressors. Students from divorced or separated family backgrounds exhibited elevated levels of suicidal ideation compared to their counterparts from intact families. Academic performance emerged as a particularly strong determinant, with students in lower CGPA categories demonstrating substantially higher levels of current suicidal ideation. Gender differences were statistically significant but modest, with female students reporting higher past suicidal ideation and male students exhibiting slightly higher current suicidal ideation. Overall, the findings highlight the multidimensional and context-dependent nature of suicidal ideation among university students. Distinguishing suicidal ideation into temporal categories provides nuanced insights that can inform targeted screening, early intervention, and evidence-based, campus-focused suicide prevention strategies within higher education institutions.